Optimal fiscal and monetary policies in a recession: Is there a way out of the trap in an open economy? - Kari E.O. Alho (The Research Institute of the Finnish Economy (ETLA), 2000)
The paper addresses the classical question how to lead the economy from a recession back to full employment in an open economy. In a recession caused by an adverse demand shock, optimal policies crucially depend on whether the income multiplier related to a policy is bigger than unity. This holds for investment, and so the optimal real interest rate is explicitly solved from the condition defined by Keynes (1936), i.e., it is that rate at which the elasticity of employment is zero. As to expansionary fiscal policies, however, the above multiplier condition is not uniformly satisfied and some controversial policy conclusions emerge. Secondly, it is shown that the optimal monetary policy requires a tax on foreign capital outflows, combined with inflationary finance. However, the optimal investment activity can also be reached by retaining international financial integration and channelling subsidies to investing firms. – – Tämä tutkimus käsittelee klassista kysymystä, miten talouspolitiikalla voidaan palata täystyöllisyyteen avoimessa taloudessa. Osoitetaan, että taantumassa, jonka on aiheuttanut kysyntäshokki, optimaalinen politiikka riippuu ratkaisevasti siitä, onko ao. politiikkaan liittyvä kerroinvaikutus suurempi kuin ykkönen. Tämä pätee tutkimuksessa rakennetussa mallissa investoinneille ja siksi optimaalinen korko voidaan ratkaista Keynesin (1936) määrittelemästä ehdosta, jonka mukaan optimaalinen korko on se, jolla vallitsee täystyöllisyys. Tämä reaalikorko johdetaan tutkimuksessa. Sen sijaan ekspansiivisen finanssipolitiikan suhteen tämä kerroinehto ei ole yleisesti voimassa, joten politiikkasuositukset ovat osittain tavanomaisesta poikkeavia. Edelleen tutkimuksessa tutkitaan sitä, miten optimaalinen korko voidaan saavuttaa käytännössä. Tämä voi tapahtua joko asettamalla vero ulkomaisille pääomaliikkeille ja harjoittamalla inflatorista rahapolitiikkaa tai toisena vaihtoehtona säilyttämällä kansainvälisten pääomaliikkeiden vapaus, mutta kanavoimalla investointitukia yrityksille. – Korko , taantuma , finanssi- ja rahapolitiikka , investoinnit
Keywords: E12; F41; 330; Interest rate; recession; fiscal and monetary policies; investment; Konjunkturpolitik; Geldpolitik; Realzins; Theorie